Biofilm formation by meat-borne Pseudomonas fluorescens on stainless steel and its resistance to disinfectants. (September 2018) - Wang, Huhu; Cai, Linlin; Li, Yunhan; Xu, Xinglian; Zhou, Guanghong
Abstract: Microorganism biofilms can form on food-contact surfaces and lead to cross-contamination of bacteria during food processing. The dynamics of biofilm formation by Pseudomonas fluorescens associated with meat spoilage and the resistance of established biofilm to four disinfectants were investigated in this study. The results indicated that more than 4.5 log CFU/cm 2 of P. fluorescens were transferred to a stainless-steel surface under short-term (5 h) scenario, and bacteria transfer occurred even after only 10 min exposure. A mature biofilm was discovered after 5 days of incubation under long-term (7 days) scenario. The biofilm was characterized by more than 9.5 log CFU/cm 2 cells, 120 μm thick and a large amount of extracellular polymeric substances. Observation of mature biofilm were further confirmed by confocal laser scanning microscopy and attenuated total reflection fourier-transformed infrared spectroscopy. The established biofilm showed distinct resistance to four disinfectants, namely sodium hypochlorite (SH), chlorine dioxide (CD), slightly acidic electrolyzed water (sAEW) and acidic electrolyzed water (AEW). The cells reduction was significant dependent on the concentrations, almost 8.0 log CFU/cm 2 of biofilm cells were reduced by 40 mg/L AEW and 200 mg/L SH treatment for 30 min, below the detection limit (1.32 log CFU/cm 2 ). However, less than 3 log CFU/cm 2 reduction of biofilm cells were obtained after treatment with 40 mg/L sAEW and 20 mg/L CD for 30 min, remaining large numbers of biofilm survival. Meanwhile, the cells reduction was time-dependent, and the numbers of surviving cells rapid declined along with increasing time, but there was no additional log reduction when treatment of 20 mg/L CD was increased from 15 to 30 min. The finding suggested that AEW has great potential to be used as an environmentally friendly intervention alternative for the elimination of P. fluorescens biofilm, substituting for the traditional sodium hypochlorite in the food industry. Highlights: Two kinds of cross-contamination scenarios in meat industry were evaluated. Formed-biofilm of P. fluorescens showed considerable tolerance to disinfectants. AEW can substitute for traditional sodium hypochlorite for eliminating biofilm.